STUDI PUSTAKA PEMANFAATAN BAHAN ALAM SEBAGAI ALTERNATIF BAHAN TAMBAHAN PANGAN - Nur Hazimah, Salma
Food additives are substances added to food for specific purpose and becoming a component of food in small amounts, due to packaging, storage, or other factors. Some food additives, namely preservatives are used to prevent decomposition due to the presence of microorganisms, food colorants to improve color, and sweeteners to give a sweet taste. Natural food additives gaining more interest related to safety and efficacy, meanwhile the use synthetic food additives in excessive amounts or continuously for a long time might be harmful to health. In this literature review, a search for alternative natural food additives is carried out based on existing studies and from this literature review, hoped data on natural potential for food preservatives, colorants, and sweeteners will be obtained. Literature researches are made through the search portals on the ScienceDirect, PubMed, Google Scholar, and ResearchGate sites. There are many plants that have the potential to be used as food additives. Arcangelisia flava and Thymus vulgaris are examples of plants that have the potential to be preservatives due to the content of phenolic compounds, alkaloids, and essential oils which have antimicrobial activity. Myrciaria jaboticaba, Genipa americana, and Beta vulgaris can be used as natural food colorant because they have anthocyanins and betalain which are natural pigment compounds. Furthermore, Glycyrrhiza glabra and Stevia rebaudiana and several palm plants are used as sweeteners because they contain sugar and other sweet compounds. Result found data on potential plants for natural food additives as many as 26 families (50 plants) with the most Lamiaceae (6 plants) for preservatives, 20 families (25 plants) with the most Cactaceae (3 plants) for colorants, and 3 families (8 plants) with the most Arecaceae (6 plants) for sweeteners. These plants are known to be safe by showing no toxicity to low toxicity. Culinary herbs and spices are potential for natural preservatives considering their effectiveness and toxicity, fruits and butterfly pea flower are potential plants for natural colorant that has been widely used which indicates the material are safe, and also thaumatin which has a high sweetness index makes these ingredients potential for natural sweeteners.